Named entity narratives - Niklas Benner; Kai-Robin Lange; Carsten Jentsch (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
While the actions of economists and politicians can be influenced by facts, statistics or empirical predictions, narratives are becoming an increasingly important factor for the decision making in the field of economics and politics. Evaluating such narratives not at selective points in time but rather as a timeline can give us an insight on the effects of changing narratives on economic processes. We propose a model to detect two distinct types of temporal narratives by evaluating the relevance of entities in a timeline of newspaper articles. This methodology is based on the fundamental concept that all narratives are driven by and centered around certain entities. We provide a model to describe entity-based time dynamic media attention and detect both temporary (events) and permanent (structural break) changes of narratives by analyzing the number of appearances of an entity and the change in word frequency surrounding it. Our model detects several meaningful events and structural breaks, such as Mario Draghi's well known 'Whatever it takes' speech in 2012 or the change of narrative surrounding Wladimir Putin due to start of the Russian-Ukrainian war in 2022. For instance, this enables us to detect the narrative shift contained in newspaper articles about the Russian Federation from being a German business partner and gas trader to being called a war mongering regime. – – Während das Handeln von Ökonomen und Politikern durch Fakten, Statistiken oder empirische Vorhersagen beeinflusst werden kann, werden Narrative zu einem immer wichtigeren Faktor für die Entscheidungsfindung in Wirtschaft und Politik. Die Bewertung solcher Narrative als Zeitstrahl statt als separierte Zeitpunkte kann uns einen Einblick in die Auswirkungen wechselnder Narrative auf wirtschaftliche Prozesse geben. Wir präsentieren ein Modell, mit dem zwei verschiedene Arten von zeitlichen Narrativen erkannt werden können, indem die Relevanz von Entitäten in einem Zeitstrahl von Zeitungsartikeln bewertet wird. Diese Methode basiert auf dem grundlegenden Konzept, dass sich alle Narrative um Entitäten herum entwickeln und eng mit diesen verbunden sind. Wir stellen ein Modell zur Beschreibung der zeitdynamischen Medienaufmerksamkeit auf der Basis von Entitäten bereit und erkennen sowohl temporäre Ereignisse (Events) als auch anhaltende Veränderungen (Strukturbrüche) von Narrativen, indem wir die Anzahl der Auftritte einer Entität und die Veränderung der sie umgebenden Worthäufigkeiten analysieren. Unser Modell erkennt mehrere bedeutsame Ereignisse und Strukturbrüche, wie etwa Mario Draghis bekannte "Whatever it takes"-Rede im Jahr 2012 oder die Veränderung des Narrativs um Wladimir Putin aufgrund des Beginns des russisch-ukrainischen Krieges im Jahr 2022. So können wir zum Beispiel die Entwicklung des Narrativs über die Russische Föderation von einem deutschen Geschäftspartner und Gashändler zu einem kriegstreibenden Regime erkennen.
Keywords: C43; C55; C89; E71; 330; Event detection; time series for count data; text mining; econometrics; narrative